Blind Watermarking Technique for Relational Database - El_Haggar, Nahla; Elkhouly, Mahmoud M.; Abu El Alla, Samah S. (COMPUSOFT: An International Journal of Advanced Computer Technology, 2024)
Recently, using of relational database system in many real life applications is increased. Therefore watermarking is considered as a vital technique for copyright protection of relational database. In this paper, we embedded watermark into some non numeric attribute. The generation of watermark depends on hash function and secret key to increase the security and the difficulty to guess by attackers. Our proposed technique is fully blind, which means that no need for the original tables to detect the watermark.